2019
DOI: 10.1007/jhep05(2019)109
|View full text |Cite
|
Sign up to set email alerts
|

The action with manifest E7 type symmetry

Abstract: We generalize Cremmer-Julia 1st order action of N = 8 supergravity with manifest E 7(7) symmetry to cases of N = 6 with manifest SO * (12) and N = 5 with manifest SU (1, 5) duality symmetries. These U dualities belong to groups of type E7 which do not admit a symmetric bilinear invariant for vector fields. Therefore the 2d order classical action derived from the one with manifest E7 type duality has a ghost vector field which, under appropriate boundary conditions, decouples. We show that when classical N ≥ 5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…See, however, Refs. [318,319] for arguments suggesting that U-duality invariance may be ultimately responsible. It is of considerable interest to settle the origin of these cancellations, and to know whether they continue to higher orders.…”
Section: Theories With N ≥ 4 Supersymmetrymentioning
confidence: 99%
“…See, however, Refs. [318,319] for arguments suggesting that U-duality invariance may be ultimately responsible. It is of considerable interest to settle the origin of these cancellations, and to know whether they continue to higher orders.…”
Section: Theories With N ≥ 4 Supersymmetrymentioning
confidence: 99%
“…Two red lines show predictions of the simplest E models. Two purple lines are for the quartic KKLTI model (66), two magenta lines show the predictions of the model (70). The set of these simple q ¼ 2 and q ¼ 5=2 attractors completely covers the sweet spot of the Planck 2018 data.…”
Section: A α Attractors and Pole Inflation: E Modelsmentioning
confidence: 93%
“…This U-duality symmetry together with maximal supersymmetry is believed to be the reason why in perturbative N ¼ 8 supergravity the UV properties are better than expected naively, and N > 4 supergravities may be even UV finite, if U-duality symmetry has no anomalies; see, for example,[65][66][67].…”
mentioning
confidence: 99%
“…They have shown that maximal supergravity behaves in UV much better than expected. It was suggested in [38][39][40] that E 7(7) symmetry together with the maximal supersymmetry of perturbative maximal supergravity in 4d might explain the cancellation of UV infinities observed in 'theoretical experiments' as described in [37]. It would be very interesting to learn more about these exceptional symmetries and their role in physics.…”
Section: Introductionmentioning
confidence: 99%